2016
DOI: 10.1007/s10554-016-0965-2
|View full text |Cite
|
Sign up to set email alerts
|

A new method to estimate pulmonary vascular resistance using diastolic pulmonary artery-right ventricular pressure gradients derived from continuous-wave Doppler velocity measurements of pulmonary regurgitation

Abstract: Purpose: Pulmonary vascular resistance (PVR) is an important hemodynamic parameter in patients with heart failure, especially when the pulmonary arterial pressure is lower due to reduced stroke volume. Several echocardiographic methods to estimate PVR have been proposed, but their applications in patients with organic left-sided heart diseases have been limited. The aim of the present study was to examine the usefulness of our new method to estimate PVR (PVR PR ) based on the continuous-wave Doppler velocity m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…A number of echocardiographic methods have been proposed for the noninvasive estimation of PVR [1][2][9][10][11][12]. However, most methods acquired formulas containing various empirical constants, which would affect the accuracy of the estimating PVR results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of echocardiographic methods have been proposed for the noninvasive estimation of PVR [1][2][9][10][11][12]. However, most methods acquired formulas containing various empirical constants, which would affect the accuracy of the estimating PVR results.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the method of Abbas et al [2] and Kaga et al [10], the new method also takes into account the contribution of RAP to estimate mPAP. Current guidelines have suggested that RAP predicts prognosis of PAH [7].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately the work presented had a great limitation because it excluded all patients with moderate and severe tricuspid regurgitation representing the population that could be most favored. In successive years, emerged publications aimed at giving validity to this equation [32][33][34][35][36], discuss its content 16-18 or establishing different approaches and hemodynamic variables for the calculation of PVR [13][14][15][16]37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of patients candidates for cardiac and liver transplant [3][4][5][6][7], is a prognostic parameter for patients with congenital diseases [8], is considered a critical parameter for evaluating PH independent of etiology [9]. The PVR is calculated invasively by the relation of the pressure gradient and the flow transpulmonar [10], Abbas and collaborators [11,12] proposed to estimate the measurement echocardiographic of the PVR by the relation TRV/TVI rvot representing the method most used currently, among others proposed for its calculation [13][14][15][16][17][18]. On the other hand, the PVRT has very precise indications according to the European Society Cardiology guidelines [9] for the diagnosis, treatment and prognosis of the PH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation